Approaching the activity limit of CoSe2 for oxygen evolution via Fe doping and Co vacancy - Yuhai Dou (Nature Portfolio, 2020)
While electronic-structure engineering lies at the heart of catalyst design, most previous studies utilize only one technique to tune the electronic states. Here, authors demonstrate that Fe doping and Co vacancy work synergistically to approach the activity limit of CoSe2 for oxygen evolution reaction.